Praktik Pemberian Makanan Bergizi dengan Bahan Pangan Lokal Kaya Zat Besi Dan Protein Guna Cegah Anemia Di SMPN 1 Kecamatan Kampar Kabupaten Kampar - Humaroh, Yola (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2025)
Adolescent girls are more vulnerable to Iron Deficiency Anemia (IDA) compared to boys due to the monthly loss of iron during menstruation. IDA can be dangerous if not properly addressed, especially in preparation for pregnancy and childbirth (Hardinsyah & Supariasa, 2017). The WHO, through the 65th World Health Assembly (WHA), has set a global target to reduce anemia in women of reproductive age by 50% by 2025. According to WHO data from 2019, the prevalence of anemia among women of reproductive age is 29.9%, which equates to over 500 million women aged 15-49 years. Based on a hemoglobin test of female adolescents at SMPN 1 Kampar in March 2022, it was found that 7 girls had mild to moderate anemia, with an average hemoglobin level of 13.2 g/dL. This community service aims to increase knowledge and positive attitudes toward nutritious food, as well as skills in processing local food rich in iron and protein to prevent anemia. The activities will be carried out from February to September 2024 at SMPN 1 Kampar, targeting teachers, parents, and students. The methods used will include counseling and practical food processing. Based on the results of the pre-test and post-test evaluation, an improvement in the scores of balanced nutrition knowledge was observed. The students successfully prepared meal plans according to the balanced nutrition guidelines and are expected to adjust their consumption patterns in line with the principles of balanced nutrition.